O papel do receptor B2 de cininas na neuroinflamação da doença de Alzheimer - Meinerz, Carine (2024)
Among the features observed in Alzheimer’s disease (AD), neuroinflammation is increasingly associated with disease progression. Bradykinin (BK), a well-established modulator of neuroinflammation, represents a promising target that may mediate this pathophysiological aspect in AD patients. This study aims to evaluate the role of the B2 kinin receptor (B2R) in neuroinflammation using both in vitro and in vivo models of the disease. Using Microarray technology, we analyzed large-scale gene expression profiles in differentiated neural progenitor cells (NPCs) derived from embryonic telencephalon (E13) of WT and APPswe/PS1dE9 transgenic mice. The transgenic neurospheres were divided into three groups: untreated (APP_WT), BKtreated (BK_APP), and HOE-140-treated (HOE_APP), to assess the effect of these treatments on gene expression. Two in vivo AD models were used: one generated by intracerebroventricular (i.c.v.) infusion of β-amyloid oligomers (AβOs) in male C57BL/6 mice, and another obtained by crossing C57BL/6 mice carrying the APPswe/PS1dE9 mutation with B2R knockout mice, generating APPswe/PS1dE9/B2R-/- transgenic mice. In the first group, some mice received i.c.v. infusion of HOE-140, a selective B2R blocker. In these models, we conducted object recognition assays, peripheral cytokine assays, quantification of glial cells in the cerebral cortex, assessment of blood-brain barrier (BBB) permeability with fluorescein, and analysis of cerebral leukocyte infiltrate by flow cytometry. In vitro assays showed significant differences (p<0.05) in the expression of 3,639, 978, and 835 transcripts between WT and APP_WT neurospheres, HOE_APP and APP_WT, and BK_APP and APP_WT, respectively. APP_WT neurospheres showed enrichment of immune response-related genes. In BK_APP neurospheres, BK enhanced the expression of these genes, suggesting an intensified inflammatory state. In contrast, HOE_APP neurospheres showed a reduction in immune gene expression, indicating that B2R blockade attenuates the inflammatory state. The results from animal models indicate that B2R blockade or absence contributes to preventing several neuroinflammation-related features in AD, including memory loss, activation of astrocytes and microglia, elevation of serum IL-6, BBB disruption, and peripheral immune cell infiltration (leukocytes, monocytes and APCs) into brain parenchyma. These findings suggest the potential of BK-related pathways as a target for complementary therapies in AD, aiding in the prevention and delay of neurodegeneration in patients with this condition.